Digenic Inheritance of PROC and SERPINC1 Mutations Contributes to Multiple Sites Venous Thrombosis - Li, Xiangui; Zhu, Jiabao; lv, Fanzhen; Ma, Wenqi; Zhou, Weimin; Zhang, Wenwen (Hämostaseologie, 2024)
Venous thromboembolism (VTE) represents a worldwide health challenge, impacting millions of people each year. The genesis of venous thrombosis is influenced in part by genetic components. Hereditary thrombosis is described as a genetically determined susceptibility to VTE. In the present study, a male patient was referred to our department presenting with multiple venous thrombosis events in different locations. Given a lack of identifiable risk factors, we aimed to investigate the possible genetic factor underlying venous thrombosis. Whole-exome sequencing was employed to examine genes linked to inherited thrombophilia in the proband. Putative variants were subsequently confirmed through Sanger sequencing within the family. The proband was identified as carrying two genetic mutations. One is the novel c.400G > C (p.E134Q) mutation affecting the final nucleotide of exon 5 in the PROC gene, potentially impacting splicing. The other is a previously reported heterozygous nonsense variant c.1016G > A (p.W339X) in the SERPINC1 gene. The proband inherited the former from her mother and the latter from her father. The presence of digenic inheritance in the patient reflects the complex phenotype of venous thrombosis and demonstrates the significance of an unbiased approach to detect pathogenic variants, especially in patients with a high risk of hereditary thrombosis.
Keywords: digenic inheritance; inherited thrombophilia; PROC gene; SERPINC1 gene; whole-exome sequencing